PENGARUH KOMPENSASI DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Perusahaan Daerah Air Minum Kabupaten Kediri) - Kurniasari, Novy (FIA UB, 2021)
This study examines the effect of compensation and organizational climate on employee performance through job satisfaction as an intervening variable for employees of local drinking water companies in Kediri. Technique data analysis used is descriptive statistics, to descriptive an object of research through sample or population data through a questionnaire distributed by the researcher then processed, tabulated in tables or in diagram form and explained in descriptive form. The data were processed using statistical tools, namely by variance-based structural equation testing or better known as Partial Least Square (PLS) using Smart PLS 2.0 software. PLS, structural model testing. This data analysis used to descriptive the compensation variables (X1), organizational climate (X2), Job Satisfaction (Z) and Employee Performance (Y), then draw conclusions from these analyzes to determine the effect of compensation and organizational climate on employee performance through job satisfaction as an intervening variable.